THE IDEOLOGY OF NON-VOILENCE: A RECONSTRUCTION OF THE PRINCIPLE OF NON-VIOLENCE AS A SOCIO-POLITICAL CULTURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Violence should be avoided. The scope for violence shouldn’t be increased. But we do not exclude. On the contrary, we constantly increase its opportunities. As a result, society and politics are not free from violence. ‘Charity begins at home.’ But we start cultivating violence in our family. The consequences have to be borne not only by the family, but also by society and the state. Social and political violence is on the rise. There is no solution. There is no socialization of the release of violence. The position of violence in the political culture is getting stronger. Political socialization is incomplete. As a result of all this, people are not safe today. Fields of liberty are also becoming limited. The problem is getting stronger. How it is possible to get rid of violence? We are trying to find the answer in this article.